Penile Reconstruction with Radial Forearm Free Flap—Present State of the Art - Vasundhra Jain; Shravan Rai K. S.; Srilekha Reddy G.; Devajyoti Guin; Shikha Gupta; Anil Murarka; Mohit Sharma (Indian Journal of Plastic Surgery, 2024)
Background Patients with congenital or acquired penile defects face significant psychological trauma. Various methods for penile reconstruction have been described of which the free radial artery forearm flap using the tube-within-tube design is found to be the most commonly used. We have assimilated the best practices described at different times in our bid to standardize the technique and have strived to make it reproducible. The reconstructed phalluses with this method can withstand the test of time, allowing the patients to lead a normal life.